Improving the effects of plasma polymerization on carbon fiber using a surface modification pretreatment. (April 2021) - Eyckens, Daniel J.; Jarvis, Karyn; Barlow, Anders J.; Yin, Yanting; Soulsby, Lachlan C.; Athulya Wickramasingha, Y.; Stojcevski, Filip; Andersson, Gunther; Francis, Paul S.; Henderson, Luke C.
Abstract: Plasma and electrochemical treatments of carbon fibers for enhanced properties are often presented in opposition to each other. This work demonstrates the combination of these methodologies through the electrochemical attachment of nitroaryl moieties to the surface of the carbon fiber, prior to the deposition of plasma polymerized acrylic acid to the surface. Notably, the tensile strength of fibers having undergone both surface modification and plasma polymerization showed a significant increase (3.76 ± 0.08 GPa), relative to control fibers (3.31 ± 0.11 GPa), while plasma polymerization alone showed no change (3.39 ± 0.09 GPa). Additional benefits resulting from both treatments were observed when determining the fiber-to-matrix adhesion. Plasma polymerization of acrylic acid alone returned a 49% increase in interfacial shear strength (IFSS) compared to control (28.3 ± 1.2 MPa vs 18.9 ± 1.2 MPa, respectively). While the presence of nitrophenyl groups on the fiber prior to polymerization conferred an additional 24% improvement over plasma polymerization alone and a 73% improvement relative to control fibers (32.7 ± 0.5 MPa vs 18.9 ± 1.2 MPa, respectively). Finally, we present the first comparison of scanning electron microscopy (SEM) and helium ion microscopy (HIM) to visualize polymers on the carbon fiber surface. HIM shows a clear advantage over conventional SEM in visualizing non-conductive coatings on carbon fibers. Analysis of the samples by X-ray photoelectron spectroscopy (XPS) confirmed the desired chemistry had been imparted onto the surface, consistent with the plasma-polymerized acrylic acid coating and presence of nitro-aryl moieties.